(untitled) (Research, Society and Development, 2026)
This article analyzes the challenges faced by families and schools in the process of including children with ASD in mainstream education. The study adopts a qualitative approach, based on a literature review and observations of everyday school practices, aiming to understand how inclusive pedagogical practices and family participation are articulated within this context. The results indicate that, despite legal and conceptual advances in the field of inclusive education, difficulties persist regarding teacher training, school institutional organization, and communication between families and schools. It is concluded that the effective inclusion of children with ASD depends on strengthening the partnership between these two spheres, investing in continuing teacher education, and adopting pedagogical practices that are sensitive to the individual needs of students.